Smurf2 knockdown attenuates the progression of diabetic nephropathy by inhibiting mesangial cell proliferation and fibrosis through suppressing EYA2 ubiquitination - Lizhen Chen; Yuqing Chen; Fei Liu; Yinhao Liu (Renal Failure, 2025)
Diabetic nephropathy (DN) is a serious microvascular complication of diabetes and the main cause of end-stage renal disease. Smurf2 is a member of ubiquitin ligases. In this study, we aimed to investigate the mechanism by which Smurf2 mediated the development of DN. C57BL/6 mice were intraperitoneally injected into streptozotocin to construct a DN mouse model, and mouse mesangial cells (MCs) were treated with high glucose (HG) to establish a cell model. A cell counting kit 8, EDU staining and Western blot assay were performed to assess cell proliferation and fibrosis. The interaction between Smurf2 and EYA2 was identified by immunoprecipitation, and the ubiquitination of EYA2 was detected by Western blot. In addition, the kidney injury of DN mice was evaluated by hematoxylin-eosin and Masson staining and the detection of biochemical parameters. Results suggested that Smurf2 expression was increased in DN mouse model and HG-treated MCs; Smurf2 knockdown inhibited cell proliferation and fibrosis in HG-treated MCs. Mechanically, Smurf2 knockdown inhibited the ubiquitination on EYA2, leading to the suppression of EYA2 degradation and an upregulation in EYA2 protein levels. Moreover, EYA2 knockdown restored cell proliferation and fibrosis in HG-treated MCs inhibited by Smurf2 knockdown. Additionally, Smurf2 knockdown inhibited kidney injury and fibrosis in DN mouse model. In conclusion, we demonstrated that Smurf2 knockdown attenuated the progression of DN by inhibiting MCs proliferation and fibrosis through suppressing EYA2 ubiquitination, which may provide a novel insight into the pathogenesis of DN.